دور الترويج السياحي في زيادة الطلب على الخدمات الفندقية: دراسة ميدانية في فنادق محافظتي حمص وطرطوس - حنا، بانة; داود، رنا إبراهيم (جامعة البعث, 2022)
يتمحور البحث في دراسة دور الترويج السياحي في زيادة الطلب على الخدمات الفندقية في فنادق محافظتي حمص وطرطوس. تم الاعتماد على المنهج الوصفي وبهدف تحليل البيانات واختبار الفرضيات تم استخدام أسلوب التحليل الإحصائي وذلك بتوزيع استبيان على عينة البحث المؤلفة من 21 فندقا تم سحبها بشكل عشوائي من الطبقات من خلال تقسيم مجتمع البحث إلى طبقات ذات معنى وتم توزيع 126 استبيان بواقع ست استبيانات في كل فندق من عينة الدراسة وكانت الاستمارات المستردة الصالحة للتحليل 100 استمارة. ومن أهم ما توصلت إليه الدراسة وجود علاقة ذات دلالة إحصائية بين الترويج السياحي بأدواته المختلفة (الإعلان، الدعاية، العلاقات العامة، تنشيط المبيعات، البيع الشخصي، التسويق المباشر) من قبل عملاء فنادق محافظتي حمص وطرطوس وزيادة الطلب على الخدمات الفندقية فيها، كما تم التوصل إلى أن التسويق المباشر مع تنشيط المبيعات من الأدوات الترويجية التي يمكن الاعتماد عليها لاحقا أكثر من غيرها لزيادة الطلب على الخدمات الفندقية في فنادق محافظتي حمص وطرطوس. وأيضا من أكثر الأدوات الترويجية الحالية تأثيرا بالعملاء لزيادة الطلب الإعلان بنسبة 23 % والدعاية بنسبة 20%، أما بقية الأدوات الترويجية فكانت بنسب أقل 18% لتنشيط المبيعات و 14% لكل من البيع الشخصي والتسويق المباشر أما العلاقات العامة فاحتلت المرتبة الأخيرة بنسبة 11%. The main objective of the research is to study the role of tourism promotion in increasing the demand for hotel services in hotels in Homs and Tartous governorates. The descriptive approach was relied upon, with the aim of analyzing the data and testing the hypotheses, the statistical analysis method was used by distributing a questionnaire to the research sample consisting of 21 hotels, which were randomly drawn from the strata by dividing the research community into meaningful strata. Of the study sample, 100 forms were valid for analysis. Among the most important findings of the study is the existence of a statistically significant relationship between tourism promotion with its various tools (advertising, publicity, public relations, sales activation, personal selling, direct marketing) by hotel clients in the governorates of Homs and Tartous and the increase in demand for hotel services there. To that direct marketing with the activation of sales is one of the promotional tools that can be relied upon later than others to increase the demand for hotel services in the hotels of Homs and Tartous governorates. And also, one of the most current promotional tools influencing customers to increase demand is advertising by 23% and advertising by 20%, while the rest of the promotional tools were at rates less 18% to stimulate sales and 14% for both personal selling and direct marketing. As for public relations, it ranked last with 11%.
Keywords: الترويج السياحي -- الخدمات الفندقية -- التنمية السياحية